KORELASI TIPE BELAJAR DENGAN MINAT BELAJAR SISWA KELAS VIII PADA MATERI SISTEM PENCERNAAN DI SMP NEGERI 1 TOMA - Duha, Endang Putri S. (TUNAS : Jurnal Pendidikan Biologi, 2024)
This study aims to investigate the relationship between learning styles and student interest in learning about the digestive system in Class VIII at SMP Negeri 1 Toma during the 2022/2023 academic year. This research is categorized as "quantitative research with a correlational approach." Correlational exploration focuses on investigating the relationships between various factors. This study also characterizes the examination of relationships among the factors tested through correlational insights. The results obtained from surveys conducted by experts indicate a significant impact between learning styles and student interest in aligning teaching and learning activities in the classroom. This aligns with the problem statement and objectives of the study, which aims to determine the relationship between specific factors, particularly learning style (X) and interest in learning (Y), using a straightforward direct relaps examination. The analysis yielded a t-value of 0.5635, which is greater than the t-table value of 0.367 at a significance level of 0.05. The conclusion of the study is that students' interest in learning is influenced by their learning styles. According to the relaps model, the equation derived is Y = 33.860 + 0.547X. This is supported by several test values: the relationship between Learning Style (X) and student interest in learning (Y) is demonstrated by the calculated r-value of 0.5635, which exceeds the r-table value of 0.367 at the 5% significance level. As professional educators, it is essential to apply various learning models and methods in teaching to enhance student interest. Additionally, teachers should pay attention to student motivation and interest, irrespective of whether students can comprehend the introduced material. If implemented effectively, this will ensure that student interest and learning outcomes meet overall evaluation guidelines.